Normal Histological Appearances of the Duodenum Jejunum and Terminal Ileum in Indonesian People - Marcellus Simadibrata; Vera Yuwono; FJW Ten Kate; GNJ Tytgat; Laurentius Lesmana; Daldiyono Daldiyono; Iwan Ariawan (The Indonesian Society for Digestive Endoscopy, 2007)
Background: There is no literature specifically on the normal appearance of small bowel mucosa amongst Indonesians. Diseases of the small bowel can cause chronic diarrhea. Chronic diarrhea is common in Indonesia. Methods: Thirty seven patients with normal stomach and small bowel on endoscopic and histopathologic examination were included in this study. Biopsies were taken from the duodenal bulb, descending part of duodenum, jejunum and terminal ileum. The scoring Method for the inflammatory cells (lymphocytes, plasma cells and eosinophil cells) was carried out using the symbols 0 (negative), +, ++, and +++. Results: The mean height of the villi of the duodenal bulb was 265.00 ± 81.89 mm, the mean height of the crypts of the duodenal bulb was 196.67 ± 56.01 mm, the mean width of the villi were 59.14 ± 74.14 mm. The mean height of the villi of the duodenum pars descendens was 317.27 ± 99.66 mm and the mean height of the crypts was 218.79 ± 84.66 mm. The mean height of the villi of the jejunum was 341.76 ± 76.06 mm and the mean height of the crypts was 189.41 ± 58.15 mm. The mean height of the villi of the terminal ileum was 235.41 ± 73.32 mm, and the mean height of the crypts was 186.22 ± 64.09 mm. Conclusion: Histologically, the mean height of the villi of the normal small bowel was between 235.41 ± 73.32 to 341.76 ± 76.06 mm and the mean height of the crypts of the normal small bowel was between 186.22 ± 64.09 to 218.79 ± 84.66 mm. Keywords: normal, duodenum, jejunum, terminal ileum, histological appearances, villous height, villous width, crypt height